PEMBUATAN MESIN PEMOTONG BATU UNTUK INDUSTRI ABSTRACT KECIL ORNAMEN BANGUNAN - Hariyanto, V Lilik (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2004)
The voucherprogramentitled"ManufacturingOrnamental StoneCuttingMachine forSmall BuildingOrnament Industries" aims toincreaseproductivityof theCV. PURBAKRIASTA especiallyin cuttingornamentalstonebeingproduced" Italsowantsto know thesize andproductivityof such ornamental stone machine.Thesteps ofthis manufacturing ornamental stonecuttingmachine areplanning,machinemanufacturing,andtraining fbr industrypartnerworkers.Theplanningstep includes:(l)designing machineplandraft,(2)calculatingtheneededmaterials,and(3)calculatingthe implementation cost. The machine-manufacturingstepincludes:(l)material cutting to fit the work draft,(2)welding,(3)assembling,(4)electricinstallation.(5)machineperformancetest, and(6)painting.The trainingfor industrypartnerworkers consistsof :(l) theory and speechdelivery,(2)demonstrationof machine using, and(3)machineusingpracticeby theindustrypartnerworkers.The result of thevoucherprogramis realization of an ornamentalstone cuttingmachine andskillachievementby theindustrypartnerworkersinthemachineoperation.The ornamentalstonecuttingmachine wasmade ofright-anglediron framesizing 80x80x7 mm,50x50x5 mm, and 30x30x3 mm, combinedwith steelplateof 3mm thick. The machine sizeis120 cm length, 60 crn width,and 190 crn height,moved by a Iphaseelectric motorpowerSEM of I HP and rotationspeed of2800RPM. The cooling systemuseswater moved by an aquariumpump.ThemachinEperformanceandproductivityespeciallyfor cuttingstraightforms has speedof 8tol0times faster comparedwith manualcutting having been doneup tillnow.Key words :stone cuttingmachine, andsmallornamentalstone industry.